2003
DOI: 10.1046/j.1365-2044.2003.03143.x
|View full text |Cite
|
Sign up to set email alerts
|

The anaesthetic management of a patient with a reninoma

Abstract: We report on the anaesthetic management of a 28-year-old woman presenting for excision of a reninoma. This is a very rare tumour of the juxtaglomerular cells of the kidney, which can be cured immediately by surgery. Previous reports have failed to record the presence or absence of perioperative cardiovascular lability. We have shown that blood pressure, cardiac index (CI) and systemic vascular resistance (SVRI) were remarkably stable in our patient throughout surgery, even during manipulation of the tumour. Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…The potential for hemodynamic fluctuations during the surgical resection of reninoma has not yet been well described. According to our observations, there were no significant fluctuations in blood pressure during the operation in any of the 9 cases, which is consistent with previous reports [29,30].…”
Section: Discussionsupporting
confidence: 93%
“…The potential for hemodynamic fluctuations during the surgical resection of reninoma has not yet been well described. According to our observations, there were no significant fluctuations in blood pressure during the operation in any of the 9 cases, which is consistent with previous reports [29,30].…”
Section: Discussionsupporting
confidence: 93%
“…Computed tomography (CT) scans were performed in 45 cases, and a renal lesion was demonstrated in all cases [4,9,11,15,18,19,21-25,27,30-32,34,35,38,40,42,43,45,47,50,51,53,54,57,59,61 -64,67, 69]. CT scans may be particularly sensitive at detecting the tumor, as shown in studies demonstrating that venous catheterization revealed lateralization in only half of 25 subjects with a lesion documented by CT [11,18,21,30,31,42,53,54,57,61,67]. Both MRI and CT scans are therefore highly effective at determining the presence of a JGA tumor.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, perioperative hemodynamic management is very important for patients who undergo surgery for the removal of a reninoma. In addition, to our best knowledge, case reports regarding the anesthetic management of a reninoma are very rare [ 4 ]. Here, we report the anesthetic management of a patient who underwent percutaneous computed tomography (CT)-guided radiofrequency ablation for the destruction of a reninoma, particularly focusing on postoperative hypotension.…”
mentioning
confidence: 99%